Pola Sebaran dan Faktor-faktor Pemilihan Lokasi Retail Kecamatan Manggala, Kota Makassar - Nofita Sari; Arifuddin Akil; Venny Veronica Natalia (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2017)
Makassar City is one of the cities of trade and services which has experienced an increase in the number of modern retailers, especially minimarkets. The number of minimarkets in Makassar City reaches 459 outlets. Manggala sub-district which is the center of integrated settlement and is one of the areas where the development of minimarkets is quite rapid. This study aims to identify retail distribution patterns and examine the factors of retail location selection in terms of distance and spatial relationships, supporting population numbers, accessibility and competition. The analytical method used is nearest neighbor analysis, kernel density, quantitative descriptive, spatial, and multiple linear regression. The results showed that based on the comparison of the three retail distribution patterns, it is known that minimarkets and stalls / shops have cluster distribution patterns but with different objectives. The grouping of minimarkets is due to competition with similar retailers or minimarkets with different brands. While the shops / stalls that are in groups are due to the ease of opening a business and most of the stalls / shops are close to the owner's house so that the grouping does not cause sharp competition. It is different from traditional markets which have a random pattern and are located in residential centers and can be reached by consumers so that there is no competition between traditional markets. After the retail location selection factor is tested the influence of these factors with multiple linear regression, it is known that these factors have an effect of 81% on retail location selection.